2009
DOI: 10.2139/ssrn.1754643
|View full text |Cite
|
Sign up to set email alerts
|

Total Factor Productivity in Indian Agriculture: Some Conceptual and Methodological Issues

Abstract: The productivity growth in agriculture is both a necessary and sufficient condition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Amidst all these efforts, slow growth and low returns of the coconut industry have been at the forefront of debate and controversy for over the decades. Many research studies in the recent past on the agriculture sector as a whole (Kalirajan et al, 1996;Saikia, 2009;Pattnaik and Shah, 2015) and on specific crops (Fogaras, 2006;Kottayi, 2008;Liu and Li, 2010;Aragon et al, 2013;Sawaneh et al, 2013), in particular, concluded that the prime factor behind the sluggishness of agricultural sector was the absence of productivity growth and stagnant technology in the sector.…”
Section: Problem Statementmentioning
confidence: 99%
“…Amidst all these efforts, slow growth and low returns of the coconut industry have been at the forefront of debate and controversy for over the decades. Many research studies in the recent past on the agriculture sector as a whole (Kalirajan et al, 1996;Saikia, 2009;Pattnaik and Shah, 2015) and on specific crops (Fogaras, 2006;Kottayi, 2008;Liu and Li, 2010;Aragon et al, 2013;Sawaneh et al, 2013), in particular, concluded that the prime factor behind the sluggishness of agricultural sector was the absence of productivity growth and stagnant technology in the sector.…”
Section: Problem Statementmentioning
confidence: 99%
“…These procedures measure the agricultural productivity without estimating a functional structure for the production function for long periods of time. However, these methods are data demanding, and their economic interpretation is not always intuitive (Saikia, 2009). In addition, productivity estimates largely depend on the index number formula (Diewert and Nakamura, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, partial productivity ignores time factor, inputs other than land, labor and capital, and secondary products while all this should be included. (Saikia, D., 2009).This proves the need to the TFP; it measures the net growth of output per unit of total inputs. This way, the TFP level is determined by the efficiency and intensity of inputs utilization in production.…”
Section: Introductionmentioning
confidence: 95%
“…Besides, the sufficient condition comes out of the production increase with a reduction in unit cost and prices. (Saikia, D., 2009).…”
Section: Introductionmentioning
confidence: 99%